2017
DOI: 10.1007/8904_2016_38
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadotropic Hypogonadism in Males with Glycogen Storage Disease Type 1

Abstract: Background: Glycogen storage disease type 1 is an autosomal recessive disorder with an incidence of 1 in 100,000. Long-term complications include chronic blood glucose lability, lactic academia, short stature, osteoporosis, delayed puberty, gout, progressive renal insufficiency, systemic or pulmonary hypertension, hepatic adenomas at risk for malignant transformation, anemia, vitamin D deficiency, hyperuricemic nephrocalcinosis, inflammatory bowel syndrome (type 1b), hypertriglyceridemia, and irregular menstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…This is in line with previous reports of low BMD values in children and adults with classical galactosemia [ 51 , 52 ] and in GSD Ia and Ib, GSD II, GSD III, GSD V, and GSD IX patients [ 53 , 54 , 55 ]. The low BMD in CHD patients could be due to their particular diet, which can result in deficiencies in certain nutrients necessary for a healthy bone density (e.g., calcium and vitamin D), due to the metabolic disorder itself [ 56 , 57 ], or as a consequence of poor metabolic control, as it has been suggested in GSD type 1 [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous reports of low BMD values in children and adults with classical galactosemia [ 51 , 52 ] and in GSD Ia and Ib, GSD II, GSD III, GSD V, and GSD IX patients [ 53 , 54 , 55 ]. The low BMD in CHD patients could be due to their particular diet, which can result in deficiencies in certain nutrients necessary for a healthy bone density (e.g., calcium and vitamin D), due to the metabolic disorder itself [ 56 , 57 ], or as a consequence of poor metabolic control, as it has been suggested in GSD type 1 [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Same results were found in males with glycogen storage disease type 1 that also occured with hypogonadotropic hypogonadism. Low level of follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone have an impact on the occurrence of several symptoms, which also includes low BMD in the lumbar region of spine, compared to hip [10]. Studies on mice showed that via estrogen substitution OPG/RANKL (osteoprotegerin/receptor activator of NF-kappa B ligand) ratio decreases which lower bone turn-over time by slowing maturation of osteoclasts and their activation [11].…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…In GSD type 1, factors contributing to the reduction in bone mineral density are poor metabolic control [ 71 , 74 , 75 ] and possibly the treatment with gCSF in GSD1b [ 74 ], though the latter relationship was not found in all studies [ 76 ]. In a recent study in 4 male GSD I (a and b) patients, all had either osteoporosis or osteopenia, suffered from hypogonadotropic hypogonadism and one patient had a spinal compression fracture at a very young age [ 75 ].…”
Section: Secondary Involvement Of the Skeletonmentioning
confidence: 99%